Robotic pyeloplasty: technological global panacea or geo-surgical nightmare? - Panagiotis Nikolinakos; Nikolaos Chatzikrachtis; Ivo Donkov; Elisavet Kotsi; Georgios Antonoglou; Ioannis Alexandrou; Nikolaos Zavras; Joseph M. Norris (Archivio Italiano di Urologia e Andrologia, 2024)
To the Editor, Pelvi-ureteric junction obstruction (PUJO) is a well-recognised clinical entity characterised by functionally significant impairment of drainage of urine at the level of the pelvi-ureteric junction due to extrinsic or intrinsic obstruction and is encountered both by adult and paediatric urologists alike. Management of PUJO has been surgical historically, and the gold standard has been an open Anderson-Hynes dismembered pyeloplasty. [...]